História da alfabetização de crianças em Goiás, 1835-1886 - Rocha, Juliano Guerra (2019)
This doctoral thesis, linked to the research line of History and Historiography of Education of the Graduate Program in Education of the Federal University of Uberlândia, has as object of study the literacy in the province of Goiás in the nineteenth century. The objective of the research was to analyze the history of the literacy of children in Goiás, comprehending the ideas about the initial teaching of reading and writing spread in schools in Goiás between 1835 and 1886. The temporal cut included the period in which the process of organizing primary education in Goiás began, through the promulgation of the first Goiás’ public education law, Law no. 13 of June 23rd, 1835, going until 1886, when it was published the last Regulation on the Public Instruction of Goiás, Act of April 2nd, 1886, led to effective compliance during the Empire. In view of this, the work developed from the following problematizations: how did the history of literacy in Goias constitute itself during the imperial period? What materials were used to literate the children of Goias throughout this history? What ideas about the initial teaching of reading and writing circulated in the province of Goiás? These questions guided the research, which was based on studies on the history of literacy, reading and books in Brazil. As a historical source, newspapers, official documents, legislations, correspondence of school files and maps of classes that were inventoried in the State Historic Archive of Goiás, as well as the Reports of the Presidents of the Province, among other documents deposited in Brazilian and European Digital Archives, were used. From these documents, a survey of the booklets and reading books used in the primary schools of the province was carried out, which made it possible to understand, through the analysis of these forms, the methods that circulated in Goiás in the nineteenth century. The research results pointed out that, contrary to the discourses that have been maintained on the public education in Goiás in the nineteenth-century in the field of literacy, there have been different attempts by the provincial government to align the proposal of primary education with the ideals of educational modernity that circulated through the national context level, especially in Rio de Janeiro. The history of literacy in Goiás was constituted by a dialogue with the educational project of a Nation, inspired by the European model. This province was not isolated, nor peripheral or interiorized, in relation to all the Empire. Goiás, in what concerns to the teaching of reading and writing, to the books and methods that subsidized this process, was in tune with the national context in the imperial regime.